INNOVATIVE ENTREPRENEURSHIP AND STARTUP IN THE CREATIVE ECONOMY - HERMAN, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper examines the theoretical aspects of innovative entrepreneurship and startup in the creative economy. An important task of any economy is to ensure rapid economic growth, which is not possible without the use of entrepreneurial innovations. Various aspects of the concept of "entrepreneurship" were considered, namely global, economic, intellectual and professional. The content of the concepts "creative entrepreneurship" and "creative economy" was analyzed. The specific origin of the creative economy is considered. Three types of creative entrepreneurship are distinguished: cultural, social and hybrid. The types of creative innovations are briefly characterized: creation of new products, improvement of previously existing ones, bringing the existing one to a new level, use of new resources, creation of a new structure. It was established that the concept of "startup" is located next to the concepts of "entrepreneurship" and "innovation". Peculiarities of a startup in the creative economy have been studied. Currently, it is known that the process of creating and developing conditions for developing and offering new products to the market begins at the startup stage. A startup is a newly created organization that uses different types of innovation. Almost all actions of a startup can be considered as experiments that test the chosen strategies. Various forms of organization of creative and entrepreneurial space in the creative economy have common characteristics.
Keywords: entrepreneurship; economy; creative economy; innovation; startup